Pegenalan Material Kontruksi Dan Teknik Penggunaannya Bagi Siswa Smk Swasta Pembda Nias - Zebua, Dermawan; Zalukhu, Muhammad Haris; Daeli, Ikhtiar Aronifati; Harita, Hamedoni; Daeli, Serta Denius; Giawa, Jun Fajar Krisman; Zebua, Friski Dermawan; Lase, Carsa Alim; Halawa, Ignasia Hastuti (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This study aims to enhance the understanding of construction materials and their applications among students at SMK Swasta Pembda Nias. In the construction industry, selecting the right materials is crucial for efficiency and project success. This study explores various materials such as concrete, wood, and steel, along with the application of effective project management methods. The findings indicate that lightweight bricks are more cost-effective and time-efficient than traditional red bricks. Furthermore, the implementation of the Project Evaluation Review Technique (PERT) and the use of measuring tools like theodolites contribute to improving students' skills in project planning and execution. Monte Carlo Simulation is also proven to be more accurate in structural reliability analysis compared to the First-Order Reliability Method (FORM). Therefore, improvements in teaching methods through practice-based approaches, technology utilization, and industry involvement are necessary to prepare students for challenges in the construction field.